Peran Pemuda Dayak Katab Kebahan Terhadap Sumberdaya Air Berkelanjutan di Desa Semadin Lengkong - Ahmad Khoiri; Eko Rudiansyah (IJEEM - Indonesian Journal of Environmental Education and Management, 2023)
This study aims to determine the role of Dayak Katab Kebahan youth in sustainable water resources in Semadin Lengkong Village. This research is a qualitative research using case study method. Methods of data collection using in-depth interviews, observation, and documentation. Data analysis techniques use data collection, data reduction, data display, and conclusions. The data validation technique uses the source triangulation technique. The results of the study show that: The role of the Dayak Kebahan youth includes collaboration, innovation, communication, evaluation and realization of sustainable programs by working together with various parties. Sustainable issues will continue to be fought for while creating a good history and protecting future civilizations by protecting springs, protecting forests, protecting the environment by protecting yourself, protecting others and protecting the earth.